A framework for coordination center responsibilities and performance in a multi-site, transdisciplinary public health research initiative. Issue 3 (14th June 2019) - Hohl, Sarah D; Knerr, Sarah; Thompson, Beti
Abstract: Funding bodies in the USA and abroad are increasingly investing in transdisciplinary research, i.e. research conducted by investigators from different disciplines who work to create novel theoretical, methodological, and translational innovations to address a common problem. Transdisciplinary research presents additional logistical and administrative burdens, yet few models of successful coordination have been proposed or substantiated, nor have performance outcomes or indicators been established for transdisciplinary coordination. This work uses the NIH-funded Transdisciplinary Research on Energetics and Cancer (TREC) Centers Initiative as a case study to put forward a working framework of transdisciplinary research coordination center (CC) responsibilities and performance indicators. We developed the framework using a sequential mixed methods study design. TREC CC functions and performance indicators were identified through key-informant interviews with CC personnel and then refined through a survey of TREC research center and funding agency investigators and staff. The framework included 23 TREC CC responsibilities that comprised five functional areas: leadership and administration, data and bioinformatics, developmental projects, education and training, and integration and self-evaluation, 10 performance outcomes and 26 corresponding performance indicators for transdisciplinary CCs. Findings revealed high levels of agreement about CC responsibilities and performance metrics across CC members and constituents. The success of multi-site, transdisciplinary research depends on effective research coordination. The functions identified in this study help clarify essential responsibilities of transdisciplinary research CCs and indicators of success of those transdisciplinary CCs. Our framework adds new dimensions to the notion of identifying and assessing CC activities that may foster transdisciplinarity.